Spatiotemporal disparities and dynamic transition characteristics of China’s national standard development contribution levels—Based on machine splitting and location assignment technology - Hongjun Sun; Yang Du; Juxiu Huang (PLoS ONE, 2025)
This study examines China’s national standard development from 2001 to 2023. Using machine splitting and location assignment technology, the Dagum Gini coefficient and its decomposition methods, and traditional and spatial Markov chain estimation methods, we identify the spatiotemporal disparities and dynamic transition characteristics of the contribution levels to national standard development across China’s eight comprehensive economic zones. The findings provide a reference for promoting regional coordinated sustainable development and high-quality economic transformation. The study reveals three key findings. (1) Contribution levels of China’s eight comprehensive economic zones to national standard development have significantly increased. The Northern Coastal comprehensive economic zone has the highest contribution levels, followed by the Eastern and Southern Coastal zones, whereas the Northwestern and Northeastern zones have lower contribution levels. (2) The overall regional disparity in national standard development contribution levels is decreasing, with the largest intraregional disparities found in the Northern and Southern Coastal zones. Significant interregional disparities persist between the Northern Coastal and Northwestern zones, the Eastern Coastal and Northwestern zones, and the Southern Coastal and Northwestern zones, with interregional disparities being the primary driver of the overall regional gap. (3) When spatial correlation effects are not considered, contribution levels exhibit clear signs of club convergence and asymmetric distribution. However, when spatial correlation effects are considered, the transition characteristics of contribution levels show significant spatial dependence. This study makes three key contributions. First, it illustrates the spatiotemporal differentiation and dynamic transition characteristics of the contribution levels of China’s eight comprehensive economic zones to national standard development, addressing gaps in existing quantitative research. Second, it introduces novel techniques and decomposition methods. Third, it identifies the primary causes of regional disparities and dynamic transition characteristics, providing empirical evidence to support policy decisions for regional coordinated sustainable development and high-quality economic transformation.